Antecedents of Innovative Work Behavior and its Impact on Business Performance - Herman Sjahruddin; Ariawan Ariawan; Hery Winoto Tj; Efendi Efendi; Tonny Yuwanda (Jurnal Manajemen Indonesia, 2024)
The aim of this study is to investigate the influence of antecedents, such as psychological empowerment and intellectual capital, on various aspects of innovative work behavior, such as idea exploration, generation, championing, and implementation, and to examine the role of each dimension in mediating the impact on business performance. The study is particularly relevant for small and medium-sized enterprises (SMEs) looking to enhance their employees' innovative behavior and optimize their business performance. A quantitative research approach was used, involving the distribution of questionnaires to 254 SMEs in West Sumatra, Indonesia, both directly and through an online survey platform. The analysis was conducted using SEM-PLS to examine the influence and mediating role of the variables. The findings demonstrate that psychological empowerment and intellectual capital have a significant effect on each dimension of innovative work behavior, with psychological empowerment acting as an antecedent and innovative work behavior as a mediator for business performance. This study contributes to the existing literature on psychological empowerment, intellectual capital, innovative work behavior, and business performance and can aid governments in formulating policies to support SMEs in improving their business performance. Keywords— Innovative Work Behavior; Business Performance